Real‐Time Wireless Detection of Heavy Metal Ions Using a Self‐Powered Triboelectric Nanosensor Integrated with an Autonomous Thermoelectric Generator‐Powered Robotic System - Yan‐Tsz Huang; Arshad Khan; Anindita Ganguly; Kuldeep Kaswan; Sreerag Suresh; Yu‐Ying Cheng; Kuan‐Ming Lee; Jui‐Han Yu; Zong‐Hong Lin (Advanced Science, 2025)
Abstract The integration of the Internet of Things (IoT) with advanced sensing technologies is transforming environmental monitoring and public health protection. In this study, a fully self‐powered and automated chemical sensing system is developed and integrated with a robotic hand for “touch and sense” detection of toxic heavy metal ions (Pb2⁺, Cr⁶⁺, As3⁺) in aquatic environments. The system combines a self‐powered solid‐liquid triboelectric nanosensor (SL‐TENS) with a thermoelectric generator (TEG), which harnesses ambient heat to power the robotic hand, eliminating the need for external power sources. The robotic hand is controlled wirelessly via an exo‐hand, minimizing the risk of exposure during remote monitoring. The sensing component uses copper oxide nanowires (CuO NWs) coated with ion‐selective membranes (ISMs) to enhance triboelectric output and enable highly selective ion detection. The system demonstrates effective real‐time, on‐site detection in lake water and data transmitted wirelessly to the user. This innovative approach provides a highly safe and efficient method for detecting hazardous pollutants in difficult‐to‐access areas, offering significant potential for wireless and real‐time environmental monitoring and hazard prevention, thus contributing to the safeguarding of human health. This study presents a novel advancement in the field of IoT‐enabled environmental monitoring systems.